Zero-fluoroscopy catheter ablation of supraventricular tachycardias in pediatric population. (19th May 2022) - Topalovic, M; Prolic Kalinsek, T; Zizek, D; Kuhelj, D; Lakic, N; Mazic, U; Jan, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Catheter ablation (CA) of supraventricular tachycardias (SVTs) in pediatric patients is conventionally performed with the aid of X-ray fluoroscopy. Usage of the three-dimensional (3D) electro-anatomical mapping (EAM) system and the intracardiac echocardiography (ICE) enables zero-fluorscopy ablation, eliminating the harmful effects of the radiation (1-3). Purpose: We retrospectively analyzed the feasibility, effectiveness and safety of zero-fluoroscopy radiofrequency and cryoablation of various types of SVTs in pediatric patients. Methods: In this retrospective study, we analyzed consecutive pediatric patients who underwent CA procedure due to SVT in our institution from April 2014 to October 2021. All procedures were performed completely without the use of fluoroscopy. A 3D EAM system and ICE were used as the principal modes of catheter visualisation. Left-sided procedures were done with ICE guided transseptal approach. Radiofrequency was the principal energy source, while cryoablation was used for arrhythmia substrates in the proximity of the conduction system. Results: The study included 174 consecutive patients (69/174 (66%) female; 12.5 ± 3.9 years; 19.2 ± 3.6 kg/m2). Altogether 176 SVTs were diagnosed and treated. Atrio-ventricular nodal reentry tachycardia (AVNRT) was diagnosed in 45% of cases (80/176), atrio-ventricular reentry tachycardia (AVRT) in 47% (82/176), focal atrial tachycardia (AT) in 7% (13/176), typical atrial flutter (AFL) was treated in only one patient, while 2 patients had multiple arrhythmias (AVNRT and AVRT). In total, 202 procedures were performed. Radiofrequency ablation was performed in 76% (154/202), cryoablation in 20% (40/202) and both in 4% (8/202) of procedures. The acute procedural success rate was 96% (195/202). Procedural success rate was 99% (79/80) for AVNRT, 94% (77/82) for AVRT, 92% (12/13) for AT, and 100% (1/1) for AFL, respectively. There were no major complications in our study group. Follow-up was complete in 99% (172/174) of patients. During the follow-up period of a median of 316 days (181 - 747), 98% of patients were arrhythmia free. On average, 1.16 procedures per patient were performed with the long-term success rate of 99% (79/80), 98% (80/82), 100% (13/13) and 100% (1) for AVNRT, AVRT, AT, and AFL, respectively. Conclusion: Zero-fluoroscopy CA of various types of SVTs in pediatric population is a feasible, effective, and safe treatment option.